The importance of using methods of analysis of the financial condition of the organization (Journal of Economic Research & Business Administration, 2016)
In this article, the author notes the importance of analyzing the financial condition of the organization both for the economy as a whole and for the enterprise. Also stated that through the analysis of the financial condition of the organization can take optimal solutions to managerial problems, only those companies whose financial condition is stable can become thriving companies. In order to begin the financial analysis, the need to analyze financial statements: report of financial condition, statement of comprehensive income, statement of cash flows, statement of changes in equity, notes. The main idea of the methods used for analysis of the financial condition of the company. It: horizontal method, direct method, trend analysis, comparative analysis, factor analysis, method of financial ratios.
Keywords: financial conditions; financial stability; accountability; solvency; methods of analysis; horizontal method; direct method; trend analysis; comparative analysis; factor analysis; method of financial ratios.